Enhancing operational efficiency: implementing business process improvement by integrating the command center in the Indonesian toll road operator company - Lea Pungky Rahayu; Ratih Dyah Kusumastuti (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Business process improvement is a well-known technique for organizations to identify processes that enhance business performance. This study aims to analyze and improve business processes in the company's principal operational processes that are directly related to controlling service requests for assistance with traffic problems on the toll road (Command Center), specifically in communication and handling requests for assistance and complaints from users of one of the toll road operators in Indonesia. Research is conducted by identifying existing processes, the underlying causes of existing problems, and analyzing business processes using the Business Process Improvement methodology and the Bizagi Modeler with Process Modeling and Notation (BPMN). An improvement within this approach is thus examined in a particular scenario. The as-is and to-be processes are measured using a technique of improvement design called the ESIA approach, consisting of four steps: eliminate, simplify, integrate, and automate. The result of the integration of Command Center services can decrease the response time for assisting requests from toll road users and enhance cost-effectiveness, improving customer satisfaction and the overall quality of toll road service.